Impact of exercise intensity on cardiac function in adolescent runners - Nie, J.; Tong, T.; Lin, H.; Shi, Q. (The Journal of Sports Medicine and Physical Fitness, 2014)
BACKGROUND: Prolonged exercise may induce a transient reduction in the left ventricular (LV) function (exercise-induced cardiac fatigue) in adults. However, data related to the cardiovascular consequences of prolonged exercise in adolescents are extremely limited. This study examined the impact of exercise intensity adopted in routine long-distance run training on LV function in trained adolescent runners in a laboratory-based setting.